In Vitro Efficacy of Quinolones and Carbapenems against Nonfermenting Gram-Negative Bacteria Isolated from Clinical Specimens in a Nepalese Tertiary Care Hospital - Shila Shrestha; Aakash Parajuli; Shiba Kumar Rai (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Nonfermenting Gram-negative bacteria (NFGNB) pose a significant public health threat due to multidrug resistance (MDR) mediated by biofilms, efflux pumps, and carbapenemases. This cross-sectional study evaluated the minimum inhibitory concentrations (MICs) of quinolones and carbapenems against the Acinetobacter calcoaceticus–baumannii (ACB) complex and Pseudomonas aeruginosa isolated from clinical specimens at the Nepal Armed Police Force Hospital, Balambu, Kathmandu, Nepal. These NFGNB were isolated and identified using standard microbiological methods. Quinolone- and carbapenem-resistant isolates, screened by disc diffusion, were tested for MICs of quinolones and carbapenems using broth microdilution. Statistical analyses were performed in SPSS v. 17.0. Ninety-two NFGNB were isolated, predominantly from urine (40.2%; 37/92). The MDR proportion was high in P. aeruginosa (85.7% [18/21] versus 80.28% [57/71]). The extensively drug-resistant (XDR) proportion was high in the ACB complex (14.1% [10/71] versus 4.8% [1/21]). The MIC 50 in P. aeruginosa against norfloxacin and ofloxacin was ≥8 and ≥0.5 µ g/mL, respectively. The MIC 50 against ciprofloxacin in P. aeruginosa was ≥8 µ g/mL, whereas it was ≥32 µ g/mL in the ACB complex. MIC 50 against levofloxacin was ≥0.5 µ g/mL in P. aeruginosa , unlike the ACB complex (≥16 µ g/mL). The MIC 50 for meropenem was lower in the ACB complex (≥4 versus ≥8 µ g/mL) than in P. aeruginosa , whereas both showed similar MIC 90 (≥64 µ g/mL). ACB complex showed higher MIC 50 against imipenem (≥4 µ g/mL) than P. aeruginosa (≥0.125 µ g/mL). Over three-fourths of the NFGNB infections were caused by the ACB complex, exhibiting high XDR rates and elevated MICs to quinolones and carbapenems, underscoring the need for strengthened antimicrobial stewardship.